2006
DOI: 10.1111/j.1440-1630.2006.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of entry level occupational therapy doctoral students towards inclusion for students with disabilities

Abstract: Background/Aims: The increasing popularity of inclusive education for students with disabilities and the attitudes towards it inevitably affect school-based occupational therapy practice. This survey study investigated the attitudes of entry-level occupational therapy doctoral (EOTD) students towards inclusive education and the effect of professional education on their perception. Methods: A total of 62 EOTD students responded to a self-developed questionnaire, Attitudes and Inclusive Education Survey, yieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
1
5
0
1
Order By: Relevance
“…Echoing the results of other studies, future pedagogues taught at the University of Valencia seem to show highly positive attitudes towards IE, even to a greater extent than their peers from other countries in similar studies (Cook, 2002;Gómez & Infante, 2004;Haq & Mundia, 2012;Mu et al, 2007). Specifically, some other countries' students show doubts or even rejection towards IE for students with sensory deficits, intellectual impairment, behavioural problems or multiple disabilities (Cook, 2002;Haq & Mundia, 2012), disabilities ); or even a more general rejection towards students with low academic performance or with a shy, withdrawn personality ).…”
Section: Future Education Professionals' Attitudes Towards Iesupporting
confidence: 55%
See 2 more Smart Citations
“…Echoing the results of other studies, future pedagogues taught at the University of Valencia seem to show highly positive attitudes towards IE, even to a greater extent than their peers from other countries in similar studies (Cook, 2002;Gómez & Infante, 2004;Haq & Mundia, 2012;Mu et al, 2007). Specifically, some other countries' students show doubts or even rejection towards IE for students with sensory deficits, intellectual impairment, behavioural problems or multiple disabilities (Cook, 2002;Haq & Mundia, 2012), disabilities ); or even a more general rejection towards students with low academic performance or with a shy, withdrawn personality ).…”
Section: Future Education Professionals' Attitudes Towards Iesupporting
confidence: 55%
“…Future professionals' general attitude towards IE is positive (Cook, 2002;Haq & Mundia, 2012;Loreman, Earle, Sharman, & Forlin, 2007;Mu, Franck, & Konz, 2007), even in spite of some professionals' stance denouncing the lack of initial training, time and assistance to address it correctly (Lambe, 2011). Future professionals show a clearer position regarding IE in the case of students with learning disabilities than in the case of students with behavioural problems, mental deficiency or multiple disability (Cook, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown how initial training on IE is determining for its success (Avramidis, & Norwich, 2002;Carpenter & Cai, 2011;Cook 2002;Jiménez-Monteagudo & Hernández-Álvarez, 2013;Mu et al 2007;Sharma et al 2006). Specific training on IE improves future teachers' attitudes and confidence and reduces their concerns (Glumbic et al 2004;Stella et al 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…además, y coincidiendo con Buendía et al (2011), la finalidad de esta titulación no es sólo la de capacitar a profesores que resuelvan situaciones educativas sino también, profesionales formados en la reflexión, resolución de problemas, investigación e innovación, que puedan contribuir a que las futuras generaciones de alumnos estén mejor preparadas para afrontar los retos que se les presenten. además, la formación docente supone un aspecto importante de cara al desarrollo de actitudes positivas (Idol, 2006;Horne y Timmons, 2009) y éxito en el desarrollo del proceso inclusivo (Carpenter y Cai, 2011;Jiménez y Hernández, 2013;Mu, Franck y Konz, 2007;Sharma, Moore y Sonawane, 2006).…”
Section: Marco Teóricounclassified